Numerical analysis on the effects of air flow in the wake of a large vehicle on trailing a passenger car - Amirnordin, Shahrin Hisham (2010)
This study focuses on the relative values of drag and lift forces acting on a passenger trailing a large vehicle (drafting) under unsteady conditions. The simulation is conducted using FLUENT CFD software for a two-dimensional flow domain at Re 3.65x106 for a trailing distance of 0 to 30 meters. The unsteady effect is studied at 15 time intervals for each time step. Turbulence is simulated using the RANS k-epsilon model. Results show that erodynamically, the critical drafting distance is between four to five meters where a sharp peak is observed for drag at five meter distance. The lowest drag is found to occur at four meters. The results show the suitable distance for drafting which may serve as useful information for vehicle fuel economy and stability.